Analisis Tingkat Kelelahan Pada Pekerja Produksi Aspal Menggunakan Metode Swedish Occupational Fatigue Index (SOFI) DI PT. Wirataco Mitra Mulia - Yuli Sarbena; Sofiyanurriyanti Sofiyanurriyanti (Fakultas Sains dan Teknologi Universitas Islam Negeri Sultan Syarif Kasim Riau, 2021)
Fatigue is a decrease in work quality, efficiency and endurance in completing work. The high workload can cause increased work fatigue experienced by PT. Wirataco Mitra Start is a company engaged in the construction of stone crushers and asphalt production using an AMP (asphalt mixing plant) machine. This study aims to determine the level of fatigue experienced by workers in the asphalt production section at PT. Wirataco Mitra Mulia where the workers have to work for 13 hours/day. Starting from 08:00-17:00 then from 02:00-08:00, with the number of workers as many as 6 people. After the analysis was carried out using the Swedish Occupational Fatigue Index (SOFI) method. The results of the SOFI questionnaire were obtained from respondent data from 6 asphalt production workers, the highest level of fatigue was obtained, which was in the medium category with a percentage of 100%. Then, based on the dimension results using the SOFI method, it is known that the highest level of fatigue felt by the workers in the asphalt production section is sleepiness with a value of 10, followed by physical exertion with a value of 6.5. Then lack of motivation (lack of motivation) with a total value of 6.5, followed by physical discomfort with a total value of 5.8, and the lowest level of fatigue is lack of energy (lack of energy) with a total value of 5.5.